New spirituality, atheism, and authenticity in Finnish underground rap - Rantakallio, Inka (fi=Turun yliopisto|en=University of Turku|, 2019)
In this dissertation, I study the discourses of new spirituality, atheism, and authenticity in Finnish underground rap in the twenty-first century. The study maps the worldviews and audiovisual aesthetics of four Finnish artists, Ameeba, Khid, Julma Henri, and RPK (the latter two forming the duo Euro Crack), while exploring larger issues such as contemporary Western religious trends and the relationship between artists, their audience, and the music industry. The study’s data consist of field research (ten interviews, observation at concerts and in social media 2013–2017), and sonic and audiovisual material (recordings, three music videos). Theoretically, the study draws from religious studies theories on Western alternative spirituality and atheism, popular musicology, hip hop studies, and theories on musical authenticity. Methodologically, the study relies on ethnographic data collection, discourse analysis, and close reading. The study indicates that while the four Finnish rappers emphasize the individuality of their worldviews, their views reflect a mixture of ideas and traditions present in contemporary Western religious landscape, including non-dualistic Eastern religions, New Age environmentalism, and scientific atheism. The artists also outline an aesthetic for their music and underground rap more generally as defying rap music, pop music, and music industry norms, as independent music making, and as drawing from alternative electronic genres and deeper philosophical content. The artists construct authenticity by claiming that their music reflects their personal worldviews and aesthetic preferences. Further, the study increases understanding about the interrelationship of rap and postmodern worldviews and advances research on the connections between popular music and religion.

Uushenkisyys, ateismi ja autenttisuus suomalaisessa underground-rapissa Väitöskirjassani tutkin 2010-luvun suomenkielistä underground-rap-musiikkia ja siinä ilmeneviä autenttisuuden, uushenkisyyden ja ateismin diskursseja. Tutkimuksen kohteena on neljä suomalaista rap-artistia (Ameeba, Khid, Julma Henri, sekä RPK, joka Julma Henrin kanssa muodostaa Euro Crack -duon), ja heidän ilmaisussaan rakentuvat maailmankatsomukset ja audiovisuaalinen estetiikka. Tutkimuksessa tarkastellaan myös laajempia kysymyksiä liittyen länsimaiseen uskontokehitykseen sekä artistien suhteeseen yleisöön ja musiikkialaan. Tutkimuksen aineisto koostuu kenttätutkimuksesta (10 haastattelua, havainnointi konserteissa ja sosiaalisessa mediassa 2013–2017) sekä äänellisestä ja audiovisuaalisesta materiaalista (äänitteet, kolme musiikkivideota). Tutkimuksen teoreettinen viitekehys hyödyntää uskontotieteen teorioita koskien länsimaista uushenkisyyttä ja ateismia, populaarimusiikintutkimusta, hiphop-tutkimusta, sekä teorioita autenttisuudesta. Menetelmällisesti tutkimus nojaa etnografisiin aineistonkeruumetodeihin sekä diskurssianalyysiin ja lähilukuun. Tutkimus osoittaa, että vaikka artistien maailmankatsomukset painottavat yksilöllisyyttä, ne heijastavat myös laajempia nykyhetken länsimaisessa uskontokentässä toisiinsa sekoittuvia ideoita ja traditioita. Näihin kuuluvat erityisesti non-dualistiset itämaiset uskonnot, New Age -vaikutteinen ympäristötietoisuus, sekä tiedeuskoon nojaava ateismi. Artistit myös rakentavat omaa sekä underground rap-musiikkia koskevan estetiikan ihannetta rap- ja pop-musiikin sekä musiikkialan normeja vastustavana, itsenäisenä, sekä elektronisista genreistä ammentavana,